Highly efficient chiral resolution of DL-arginine by cocrystal formation followed by recrystallization under preferential-enrichment conditions - Iwama, Sekai; Kuyama, Kazunori; Mori, Yuko; Manoj, Kochunnoonny; Gonnade, Rajesh G.; Suzuki, Katsuaki; Hughes, Colan E.; Williams, P. Andrew; Harris, Kenneth D. M.; Veesler, Stephane; Takahashi, Hiroki; Tsue, Hirohito; et al. (Chemistry-A European Journal, 2014)
An excellent chiral symmetry-breaking spontaneous enantiomeric resolution phenomenon, denoted preferential enrichment, was observed on recrystallization of the 1:1 cocrystal of dl-arginine and fumaric acid, which is classified as a racemic compound crystal with a high eutectic ee value (>95%), under non-equilibrium crystallization conditions. On the basis of temperature-controlled video microscopy and in situ time-resolved solid-state (CNMR)-C-13 spectroscopic studies on the crystallization process, a new mechanism of phase transition that can induce preferential enrichment is proposed.
Keywords: Amino acids; chiral resolution; cocrystals; Crystal growth; phase transitions

Preferential enrichment of DL-leucine using cocrystal formation with oxalic acid under nonequilibrium crystallization conditions - Manoj, Kochunnoonny; Takahashi, Hiroki; Morita, Yoko; Gonnade, Rajesh G.; Iwama, Sekai; Tsue, Hirohito; Tamura, Rui (Chirality, 2015)
By utilizing the preferential enrichment (PE) technique, we achieved an improved enantiomeric resolution of DL-leucine (Leu) using a 1:1 cocrystal (DL-1) of DL-Leu and oxalic acid. The crystal structure analysis of DL-1 indicated the occurrence of a novel type of phase transition and subsequent preferential redissolution of one enantiomer from the resulting crystals into solution. Chirality 27:405-410 2015. (c) 2015 Wiley Periodicals, Inc.
Keywords: chiral resolution; cocrystal formation; leucine; phase transition; preferential enrichment

Crystal structure analysis of highly efficient chiral resolution of (RS)-arginine-fumaric acid cocrystal under preferential enrichment conditions - Manoj, Kochunnoonny; Takahashi, Hiroki; Iwama, Sekai; Gonnade, G. Rajesh; Tsue, Hirohito; Tamura, Rui (Journal of Molecular Structure, 2021)
Two new hydrate cocrystals, (RS)-arginine-fumaric acid-H2O ( 2 ) and (S)-arginine-2 fumaric acid-H2O ( 3 ), were obtained by the slow evaporation of the saturated aqueous ethanol solution of a 1:1 mixture of S-enriched arginine (33% ee) and fumaric acid or (S)-arginine and fumaric acid, respectively. Cocrystals 2 and 3 possess an isostructural molecular organization containing homochiral 1D chains of arginine sim-ilar to that of the anhydrous cocrystal of (RS)-arginine-fumaric acid ( 1 ). The latter showed an efficient ``preferential enrichment (PE)'', a unique spontaneous enantiomeric resolution phenomenon by simple recrystallization from the highly supersaturated solution. The formation of unstable cocrystals 2 and 3 seems to have played a crucial role in the enrichment of arginine in the mother liquor under PE crystal-lization conditions. (c) 2021 Elsevier B.V. All rights reserved.
Keywords: Arginine; cocrystals; crystal structure; Enantiomeric resolution; preferential enrichment